2018
DOI: 10.1159/000494449
|View full text |Cite
|
Sign up to set email alerts
|

Fetal But Not Maternal Angiotensin Converting Enzyme (ACE)-2 Gene Rs2074192 Polymorphism is Associated with Increased Risk of Being a Small For Gestational Age (SGA) Newborn

Abstract: Background/Aims: The maternal and fetal Renin-Angiotensin-System is involved in the control of pregnancy outcomes such as blood pressure control and gestational age. However, very little is known about the impact of the angiotensin converting enzyme 2 (ACE2) on pregnancy outcome. We thus performed a prospective clinical observational study analyzing the association of maternal and fetal ACE2 gene rs2074192 polymorphism with fetal growth during pregnancy. Methods: 898 singleton pregnant women were prospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Fetal plasma levels of Ang-(1–7) in the term group were 11-fold higher than Ang II (900 compared with 80 pM) as assessed by separate ELISAs and a similar concentration range for Ang-(1–7) and Ang II was reported for the maternal circulation [109]. Moreover, this group has recently reported that the fetal but not maternal ACE2 polymorphism rs2074192 associated with lower birth weight [113]. We have examined the effects of perinatal programming on future cardiovascular health in a prospective cohort of individuals born preterm with very low birth weight compared with a term-born control cohort and show that alterations in the Ang-(1–7) pathway persist into adolescence and young adulthood.…”
Section: Ang-(1–7) Programming–human Studiesmentioning
confidence: 74%
“…Fetal plasma levels of Ang-(1–7) in the term group were 11-fold higher than Ang II (900 compared with 80 pM) as assessed by separate ELISAs and a similar concentration range for Ang-(1–7) and Ang II was reported for the maternal circulation [109]. Moreover, this group has recently reported that the fetal but not maternal ACE2 polymorphism rs2074192 associated with lower birth weight [113]. We have examined the effects of perinatal programming on future cardiovascular health in a prospective cohort of individuals born preterm with very low birth weight compared with a term-born control cohort and show that alterations in the Ang-(1–7) pathway persist into adolescence and young adulthood.…”
Section: Ang-(1–7) Programming–human Studiesmentioning
confidence: 74%
“…Both human and animal studies have shown that the use of ACE inhibitors in early pregnancy can cause maternal weight loss and decreased blood pressure, uterine blood flow and amniotic fluid production, followed by fetal hypotension or death. The most common adverse effects of ACE inhibitors in the second or third trimester of pregnancy included intrauterine growth retardation, neonatal hypotension, renal failure, oligohydramnios, patent ductus arteriosus and pulmonary hypoplasia 12 Other studies have found that an ACE2 gene polymorphism in pregnant women is associated with recurrent abortion and fetal growth restriction 13,14 . Thus, SARS‐CoV‐2 infection in women is likely to cause adverse reactions similar to those caused by ACE2 inhibitors or ACE2 gene polymorphism in pregnant women and their fetuses.…”
Section: Hypoxia and A Decrease In Ace2 Content In Pregnant Women Witmentioning
confidence: 99%
“…Several reports from the literature, have indicated that ACE 2 is highly expressed in the reproductive organs, placenta, uterus and, maternal-fetal interface during pregnancy; which is important for normal fetal growth and also for regulation of the Ang II level. Besides, renal ACE 2 is also upregulated in pregnant women, further in comparison; the placenta shows the highest expression of renal ACE 2 mRNA, followed by kidney and, then the uterus; whereas, the ACE 2 activity is higher in kidney in comparison to placenta and uterus ( Table 1 ) [ [11] , [12] , [13] , [14] ].…”
Section: Introductionmentioning
confidence: 99%